PENGARUH PELATIHAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA GIANT EKSTRA SEMPU KOTA SERANG - Ubay Haki (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2021)
The aim of the research title was to know whether the training influence and service quality effect to consumer satisfaction in Giant Ekstra Sempu Serang city. The hypothesis test used description quantitative method. The population of this research was consumers who shop at Extra Giants Sempu Serang city by the amount 800 people, in taking the samples using Slovin formula found 89 people. To get the data, this study used observation, distributed questionnaires and interviews. The data analysis technique used for processing the data was likert scaale and was assisted by SPSS 24 tool, therefore from research results could be seen the correlation coefficient value between training grades and service quality on consumer satisfaction was 0,827 (very strong), the coefficient of determination was 0,823 or 82,7%, that described the value of training (X1) and service quality(X2) contributed for 82,7% to costumer satisfaction (Y), while the remaining of 17,3% was influenced by other variables out of this study. The results of this study showed (1) there was a positive and significant effect the value of training on costumer satisfaction at 3,015, (2) there was a positive and significant influences quality of service to customer satisfaction at 4,485, (3) there was a positive and significant influence of the value of training and simultaneous service quality on customer satisfaction at 205,647